Managing Open Innovation in SMEs: A Good Practice Example of a German Software Firm - Brunswicker, Sabine; Ehrenmann, Frank (International Journal of Industrial Engineering and Management, 2013)
In recent years the open innovation paradigmhas gained great attention in research on innovation and strategic management. Current research indicates that firms are opening up their innovation processes and adapt their business models to benefit not only from internal but also from external ideas and knowledge. So far, most of the research on open innovation has been focused on open innovation practices in large firms and has not considered open innovation in SMEs adequately. For this reason, our paper investigates organizational capabilities for managing open innovation in SMEs. Based on a case study analysis of the company CAS Software AG the researchersargue that SMEs have to build up new managerial capabilities within six dimensions of an integrated managerial system for open innovation. In addition the paper revealsthe prosperous transformation process of the CAS Software AG towards an open innovator highlighting itscharacteristicof a guided evolutionby means of a maturity model. Article history: Received (18 November 2012); Revised (25 December 2012); Accepted (16 January 2013)